Models of dynamic programming to determine the optimal solution with the help of investment (Journal of Economic Research & Business Administration, 2016)
The main thing today in the management of the investment portfolio as well as the placement of investment resources in the period of its implementation is considered as asset management mechanism. If you look at the level of investment risk in our country, there is the probability of profit or lack thereof. Despite its potential advantages and disadvantages of dynamic resource allocation mechanism can be applied to a number of issues. Investment managers thanks to a dynamic strategy makes it possible to change the overall profitability of the distribution structure. In the dynamic form altering the types of relationships the amount of assets, the investor can monitor the benefits of reducing the risk of return. And it can directly enter in the strategy «to limit the risk of deficiency» and to harmonize the distribution of the yield structure most suitable. Therefore, to explore the market, the return on investment depends on market conditions (positive or negative). With this in mind, this article provides solutions using dynamic programming model of optimal investment elements.
Keywords: portfolio management; exchange of resources; dynamic management; adaptive; asset investment; dynamic programming.